The Effect of Work Stress and Leadership Style on Turnover Intention CV. Gulamali Tasikmalaya - Soraya Soraya; Cece Rakhmat; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2023)
This research aims to determine the effect of work stress, leadership style on turnover intention. The method used is a quantitative method with a sample of 43 respondents from cv Gulamali Tasikmalaya. The data used are primary data and secondary data. The analytical tool used is multiple linear regression analysis using SPSS version 25. The results of this study indicate that simultaneously work stress and leadership style have a significant effect on turnover intention. Partially, work stress has a significant effect on turnover intention. Partially, leadership style has no effect on turnover intention.